Exploring the potential of agricultural system change as an integrated adaptation strategy for water and food security in the Indus basin - Smolenaars, Wouter Julius; Jamil, Muhammad Khalid; Dhaubanjar, Sanita; Lutz, Arthur F.; Immerzeel, Walter; Ludwig, Fulco; Biemans, Hester (Environment, development and sustainability, 2024)
Water security and food security in the Indus basin are highly interlinked and subject to severe stresses. Irrigation water demands presently already exceed what the basin can sustainably provide, but per-capita food availability remains limited. Rapid population growth and climate change are projected to further intensify pressure on the interdependencies between water and food security. The agricultural system of the Indus basin must therefore change and adapt to be able to achieve the associated Sustainable Development Goals (SDGs). The development of robust policies to guide such changes requires a thorough understanding of the synergies and trade-offs that different strategies for agricultural development may have for water and food security. In this study, we defined three contrasting trajectories for agricultural system change based on a review of scientific literature on regional agricultural developments and a stakeholder consultation workshop. We assessed the consequences of these trajectories for water and food security with a spatially explicit modeling framework for two scenarios of climatic and socio-economic change over the period 1980–2080. Our results demonstrate that agricultural system changes can ensure per capita food production in the basin remains sufficient under population growth. However, such changes require additional irrigation water resources and may strongly aggravate water stress. Conversely, a shift to sustainable water management can reduce water stress but has the consequence that basin-level food self-sufficiency may not be feasible in future. This suggests that biophysical limits likely exist that prevent agricultural system changes to ensure both sufficient food production and improve water security in the Indus basin under strong population growth. Our study concludes that agricultural system changes are an important adaptation mechanism toward achieving water and food SDGs, but must be developed alongside other strategies that can mitigate its adverse trade-offs.